Feed-thickening practices in NICUs in the current era: Variability in prescription and implementation patterns. Issue 6 (December 2015) - Madhoun, Lauren L.; Siler-Wurst, Kimberly K.; Sitaram, Swetha; Jadcherla, Sudarshan R.
Abstract: Background: Feed-thickening for infants in the Neonatal Intensive Care Unit (NICU) is performed due to concerns of dysphagia and gastroesophageal reflux disease (GERD). No standards currently exist regarding feed-thickening prescriptions and practices and this results in variable and potentially unsafe feeding approaches. Methods: Electronic surveys were sent to neonatal feeding therapists and providers in order to determine the prescriptions and practices currently being used for feed-thickening in the NICU. Results: A total of 313 responses were collected. Results revealed the majority of providers use thickened feeds for concerns of dysphagia or GERD with some reporting they thicken expressed breast milk. Variability of thickening prescriptions was noted regarding consistencies, thickening agents, and recipes used. Reported approaches for measuring, mixing, and warming thickened feeds varied. Conclusion: Variability was noted in the feed-thickening prescriptions and practices performed in the NICU. Further research and standardization are required to develop thickening guidelines.